STEAM to R-SLAMET Modification: An Integrative Thematic Play Based Learning with R-SLAMETS Content in Early Child-hood Education - Hapidin; Gunarti, Winda; Pujianti, Yuli; Siti Syarah, Erie (Jurnal Pendidikan Usia Dini, 2020)
STEAM-based learning is a global issue in early-childhood education practice. STEAM content becomes an integrative thematic approach as the main pillar of learning in kindergarten. This study aims to develop a conceptual and practical approach in the implementation of children's education by applying a modification from STEAM Learning to R-SLAMET. The research used a qualitative case study method with data collection through focus group discussions (FGD), involving early-childhood educator's research participants (n = 35), interviews, observation, document analysis such as videos, photos and portfolios. The study found several ideal categories through the use of narrative data analysis techniques. The findings show that educators gain an understanding of the change in learning orientation from competency indicators to play-based learning. Developing thematic play activities into continuum playing scenarios. STEAM learning content modification (Science, Technology, Engineering, Art and Math) to R-SLAMETS content (Religion, Science, Literacy, Art, Math, Engineering, Technology and Social study) in daily class activity. Children activities with R-SLAMETS content can be developed based on an integrative learning flow that empowers loose part media with local materials learning resources. Keyword: STEAM to R-SLAMETS, Early Childhood Education, Integrative Thematic Learning References Ali, E., Kaitlyn M, C., Hussain, A., & Akhtar, Z. (2018). the Effects of Play-Based Learning on Early Childhood Education and Development. Journal of Evolution of Medical and Dental Sciences, 7(43), 4682–4685. https://doi.org/10.14260/jemds/2018/1044 Ata Aktürk, A., & Demircan, O. (2017). A Review of Studies on STEM and STEAM Education in Early Childhood. Journal of Kırşehir Education Faculty, 18(2), 757–776. Azizah, W. A., Sarwi, S., & Ellianawati, E. (2020). Implementation of Project -Based Learning Model (PjBL) Using STREAM-Based Approach in Elementary Schools. Journal of Primary Education, 9(3), 238–247. https://doi.org/10.15294/jpe.v9i3.39950 Badmus, O. (2018). Evolution of STEM, STEAM and STREAM Education in Africa: The Implication of the Knowledge Gap. In Contemporary Issues in Science, Technology, Engineering, Arts and Mathematics Teacher Education in Nigeria. Björklund, C., & Ahlskog-Björkman, E. (2017). Approaches to teaching in thematic work: early childhood teachers’ integration of mathematics and art. International Journal of Early Years Education, 25(2), 98–111. https://doi.org/10.1080/09669760.2017.1287061 Broadhead, P. (2003). Early Years Play and Learning. In Early Years Play and Learning. https://doi.org/10.4324/9780203465257 Canning, N. (2010). The influence of the outdoor environment: Den-making in three different contexts. European Early Childhood Education Research Journal, 18(4), 555–566. https://doi.org/10.1080/1350293X.2010.525961 Clapp, E. P., Solis, S. L., Ho, C. K. N., & Sachdeva, A. R. (2019). Complicating STEAM: A Critical Look at the Arts in the STEAM Agenda. Encyclopedia of Educational Innovation, 1–4. https://doi.org/10.1007/978-981-13-2262-4_54-1 Colucci, L., Burnard, P., Cooke, C., Davies, R., Gray, D., & Trowsdale, J. (2017). Reviewing the potential and challenges of developing STEAM education through creative pedagogies for 21st learning: how can school curricula be broadened towards a more responsive, dynamic, and inclusive form of education? BERA Research Commission, August, 1–105. https://doi.org/10.13140/RG.2.2.22452.76161 Conradty, C., & Bogner, F. X. (2018). From STEM to STEAM: How to Monitor Creativity. Creativity Research Journal, 30(3), 233–240. https://doi.org/10.1080/10400419.2018.1488195 Conradty, C., & Bogner, F. X. (2019). From STEM to STEAM: Cracking the Code? How Creativity & Motivation Interacts with Inquiry-based Learning. Creativity Research Journal, 31(3), 284–295. https://doi.org/10.1080/10400419.2019.1641678 Cook, K. L., & Bush, S. B. (2018). Design thinking in integrated STEAM learning: Surveying the landscape and exploring exemplars in elementary grades. School Science and Mathematics, 118(3–4), 93–103. https://doi.org/10.1111/ssm.12268 Costantino, T. (2018). STEAM by another name: Transdisciplinary practice in art and design education. Arts Education Policy Review, 119(2), 100–106. https://doi.org/10.1080/10632913.2017.1292973 Danniels, E., & Pyle, A. (2018). Defining Play-based Learning. In Encyclopedia on Early Childhood Development (Play-Based, Issue February, pp. 1–5). OISE University of Toronto. DeJarnette, N. K. (2018). Implementing STEAM in the Early Childhood Classroom. European Journal of STEM Education, 3(3), 1–9. https://doi.org/10.20897/ejsteme/3878 Dell’Erba, M. (2019). Policy Considerations for STEAM Education. Policy Brief, 1–10. Doyle, K. (2019). The languages and literacies of the STEAM content areas. Literacy Learning: The Middle Years, 27(1), 38–50. http://proxy.libraries.smu.edu/login?url=http://search.ebscohost.com/login.aspx?direct=true&db=eue&AN=133954204&site=ehost-live&scope=site Edwards, S. (2017). Play-based learning and intentional teaching: Forever different? Australasian Journal of Early Childhood, 42(2), 4–11. https://doi.org/10.23965/ajec.42.2.01 Faas, S., Wu, S.-C., & Geiger, S. (2017). The Importance of Play in Early Childhood Education: A Critical Perspective on Current Policies and Practices in Germany and Hong Kong. Global Education Review, 4(2), 75–91. Fesseha, E., & Pyle, A. (2016). Conceptualising play-based learning from kindergarten teachers’ perspectives. International Journal of Early Years Education, 24(3), 361–377. https://doi.org/10.1080/09669760.2016.1174105 Finch, C. R., Frantz, N. R., Mooney, M., & Aneke, N. O. (1997). Designing the Thematic Curriculum: An All Aspects Approach MDS-956. 97. Gess, A. H. (2019). STEAM Education. STEAM Education, November, 2011–2014. https://doi.org/10.1007/978-3-030-04003-1 Gronlund, G. (n.d.). “ Addressing Standards through Play-Based Learning in Preschool and Kindergarten .” Gronlund, G. (2015). Planning for Play-Based Curriculum Based on Individualized Goals to Help Each Child Thrive in Preschool and Kindergarten Gaye Gronlund. Gull, C., Bogunovich, J., Goldstein, S. L., & Rosengarten, T. (2019). Definitions of Loose Parts in Early Childhood Outdoor Classrooms: A Scoping Review. The International Journal of Early Childhood Education, 6(3), 37–52. Hapidin, Pujianti, Y., Hartati, S., Nurani, Y., & Dhieni, N. (2020). The continuous professional development for early childhood teachers through lesson study in implementing play based curriculum (case study in Jakarta, Indonesia). International Journal of Innovation, Creativity and Change, 12(10), 17–25. Hennessey, P. (2016). Full – Day Kindergarten Play-Based Learning : Promoting a Common Understanding. Education and Early Childhood Development, April, 1–76. gov.nl.ca/edu Henriksen, D. (2017). Creating STEAM with Design Thinking: Beyond STEM and Arts Integration. Steam, 3(1), 1–11. https://doi.org/10.5642/steam.20170301.11 Inglese, P., Barbera, G., La Mantia, T., On, P., Presentation, T., Reid, R., Vasa, S. F., Maag, J. W., Wright, G., Irsyadi, F. Y. Al, Nugroho, Y. S., Cutter-Mackenzie, A., Edwards, S., Moore, D., Boyd, W., Miller, E., Almon, J., Cramer, S. C., Wilkes-Gillan, S., … Halperin, J. M. (2014). Young Children’s Play and Environmental Education in Early Childhood Education. PLoS ONE, 2(3), 9–25. https://doi.org/10.1586/ern.12.106 Jacman, H. (2012). Early Education Curriculum. Pedagogical Development Unit, FEBRUARY 2011, 163. https://www.eursc.eu/Syllabuses/2011-01-D-15-en-4.pdf Jay, J. A., & Knaus, M. (2018). Embedding play-based learning into junior primary (Year 1 and 2) Curriculum in WA. Australian Journal of Teacher Education, 43(1), 112–126. https://doi.org/10.14221/ajte.2018v43n1.7 Kennedy, A., & Barblett, L. (2010). Supporting the Early Years Learning Framework. Research in Practise Series, 17(3), 1–12. Keung, C. P. C., & Cheung, A. C. K. (2019). Towards Holistic Supporting of Play-Based Learning Implementation in Kindergartens: A Mixed Method Study. Early Childhood Education Journal, 47(5), 627–640. https://doi.org/10.1007/s10643-019-00956-2 Keung, C. P. C., & Fung, C. K. H. (2020). Exploring kindergarten teachers’ pedagogical content knowledge in the development of play-based learning. Journal of Education for Teaching, 46(2), 244–247. https://doi.org/10.1080/02607476.2020.1724656 Krogh, S., & Morehouse, P. (2014). The Early Childhood Curriculum : Inquiry Learning Through Integration. Liao, C. (2016). From Interdisciplinary to Transdisciplinary: An Arts-Integrated Approach to STEAM Education. Art Education, 69(6), 44–49. https://doi.org/10.1080/00043125.2016.1224873 Lillard, A. S., Lerner, M. D., Hopkins, E. J., Dore, R. A., Smith, E. D., & Palmquist, C. M. (2013). The impact of pretend play on children’s development: A review of the evidence. Psychological Bulletin, 139(1), 1–34. https://doi.org/10.1037/a0029321 Maxwell, L. E., Mitchell, M. R., & Evans, G. W. (2008). Effects of Play Equipment and Loose Parts on Preschool Children’s Outdoor Play Behavior: An Observational Study and Design Intervention. Children, Youth and Environments, 18(2), 37–63. McLaughlin, T., & Cherrington, S. (2018). Creating a rich curriculum through intentional teaching. Early Childhood Folio, 22(1), 33. https://doi.org/10.18296/ecf.0050 Mengmeng, Z., Xiantong, Y., & Xinghua, W. (2019). Construction of STEAM Curriculum Model and Case Design in Kindergarten. American Journal of Educational Research, 7(7), 485–490. https://doi.org/10.12691/education-7-7-8 Milara, I. S., Pitkänen, K., Laru, J., Iwata, M., Orduña, M. C., & Riekki, J. (2020). STEAM in Oulu: Scaffolding the development of a Community of Practice for local educators around STEAM and digital fabrication. International Journal of Child-Computer Interaction, 26, 100197. https://doi.org/10.1016/j.ijcci.2020.100197 Moomaw, S. (2012). STEM Begins in the Early Years. School Science and Mathematics, 112(2), 57–58. https://doi.org/10.1111/j.1949-8594.2011.00119.x Peng, Q. (2017). Study on Three Positions Framing Kindergarten Play-Based Curriculum in China: Through Analyses of the Attitudes of Teachers to Early Linguistic Education. Studies in English Language Teaching, 5(3), 543. https://doi.org/10.22158/selt.v5n3p543 Pyle, A., & Bigelow, A. (2015). Play in Kindergarten: An Interview and Observational Study in Three Canadian Classrooms. Early Childhood Education Journal, 43(5), 385–393. https://doi.org/10.1007/s10643-014-0666-1 Pyle, A., & Danniels, E. (2017). A Continuum of Play-Based Learning: The Role of the Teacher in Play-Based Pedagogy and the Fear of Hijacking Play. Early Education and Development, 28(3), 274–289. https://doi.org/10.1080/10409289.2016.1220771 Quigley, C. F., Herro, D., & Jamil, F. M. (2017). Developing a Conceptual Model of STEAM Teaching Practices. School Science and Mathematics, 117(1–2), 1–12. https://doi.org/10.1111/ssm.12201 Ridgers, N. D., Knowles, Z. R., & Sayers, J. (2012). Encouraging play in the natural environment: A child-focused case study of Forest School. Children’s Geographies, 10(1), 49–65. https://doi.org/10.1080/14733285.2011.638176 Ridwan, A., Rahmawati, Y., & Hadinugrahaningsih, T. (2017). Steam Integration in Chemistry Learning for Developing 21st Century Skills. MIER Journail of Educational Studies, Trends & Practices, 7(2), 184–194. Rolling, J. H. (2016). Reinventing the STEAM Engine for Art + Design Education. Art Education, 69(4), 4–7. https://doi.org/10.1080/00043125.2016.1176848 Sancar-Tokmak, H. (2015). The effect of curriculum-generated play instruction on the mathematics teaching efficacies of early childhood education pre-service teachers. European Early Childhood Education Research Journal, 23(1), 5–20. https://doi.org/10.1080/1350293X.2013.788315 Sawangmek, S. (2019). Trends and Issues on STEM and STEAM Education in Early Childhood. Képzés És Gyakorlat, 17(2019/3-4), 97–106. https://doi.org/10.17165/tp.2019.3-4.8 Science, A. I. (n.d.). STEM Project-Based Learning. Spencer, R., Joshi, N., Branje, K., Lee McIsaac, J., Cawley, J., Rehman, L., FL Kirk, S., & Stone, M. (2019). Educator perceptions on the benefits and challenges of loose parts play in the outdoor environments of childcare centres. AIMS Public Health, 6(4), 461–476. https://doi.org/10.3934/publichealth.2019.4.461 Taylor, J., Bond, E., & Woods, M. (2018). A Multidisciplinary and Holistic Introduction. Varun A. (2014). Thematic Approach for Effective Communication in Early Childhood Education Thematic Approach for effective communication in ECCE. International Journal of Education and Psychological Research (IJEPR), 3(3), 49–51. https://www.researchgate.net/publication/289868193 Wang, X., Xu, W., & Guo, L. (2018). The status quo and ways of STEAM education promoting China’s future social sustainable development. Sustainability (Switzerland), 10(12). https://doi.org/10.3390/su10124417 Whitebread, D. D. (2012). The Importance of Play. Toy Industries of Europe, April, 1–55. https://doi.org/10.5455/msm.2015.27.438-441 Wong, S. M., Wang, Z., & Cheng, D. (2011). A play-based curriculum: Hong Kong children’s perception of play and non-play. International Journal of Learning, 17(10), 165–180. https://doi.org/10.18848/1447-9494/cgp/v17i10/47298 Zosh, J. M., Hopkins, E. J., Jensen, H., Liu, C., Neale, D., Hirsh-Pasek, K., Whitebread, Solis, S. L., & David. (2017). Learning through play : a review of the evidence (Issue November). The LEGO Foundation.